Molecular Evaluation of High Fluoroquinolone Resistant Genes in Endemic Cases of Shigellosis, Northeast Part of Karnataka, India - Prabhurajeshwar C (Ubiquity Press, 2017)
Objectives Shigellosis is an acute infection of the intestine caused by bacteria in the genus 'Shigella' and also an important cause of diarrhea in developing countries. This study was carried out to find the extent and nature of the emerging resistance in north part of Karnataka, India, and surrounding region with huge population, and also focused on the molecular mechanism of development of resistance against different generations of fluoroquinolones and explored the diversity of restriction endonucleases; we also tried to establish the significance of reduced minimal inhibitory concentrations (MIC) values. Methods A total of 32 multidrug-resistant 'Shigella' species (isolated from infants’ stools) were subjected to MICs of fluoroquinolone-resistant isolates done by both broth dilution and E-test method. The genes implicated in resistance to fluoroquinolone generations ciprofloxacin, ofloxacin, and gatifloxacin (gyrA, gyrB, parC, and parE) were amplified using polymerase chain reaction (PCR) method and restriction digestion analysis of PCR product were performed using PvuI and HaeII enzymes. Findings Fluoroquinolone-resistant 'Shigella' species (n = 32) comprising 'S dysenteriae', 'S flexneri', and 'S sonnei' were selected for MIC; 90.6% (29/32), 93.75% (30/32), and 93.75% (30/32) of isolates were ciprofloxacin, ofloxacin, and gatifloxacin resistant and showed the MIC range from 4-128 μg/mL. The PCR amplification results were positive for all species and asserted the presence of gyrA, gyrB, parC, and pare and sizes of the amplified products. The restriction banding patterns of amplified resistant genes were employed to detect differences among the 'Shigella' species. Conclusions The present study found that the genetic basis and its characterization of fluoroquinolone resistance in 'Shigella' isolates was considered for the common resistant genes, namely, gyrA, gyrB, parC, and pare, and had mutations at position 83 of gyrA and at position 80 of parC of the quinolone-resistant determining regions and associated molecular mechanism. Our study beneficial in identification of the causative agents of the infections, careful control and cautions use of antibiotics must be promoted, particularly to monitor the emergence of isolates that are fully resistant to fluoroquinolones.